Pulverization characteristics of coal affected by magmatic intrusion and analysis of the abnormal gas desorption index on drill cuttings - Er-Tao Chen; Liang Wang; Yuan-Ping Cheng; Hai-Jun Guo; Cong-Meng Hao; Yu-Xiao Qi; Fei Liu (Adsorption Science & Technology)
The gas desorption index of drill cuttings is a basic index that measures the initial desorption capacities of coal seams and predicts coal seam gas outbursts. Following a long period of gas drainage in the No.7 coal seam of the No.86 mining area in the Haizi coal mine, the gas desorption index of drill cuttings was still found to be much higher than the threshold value for outburst risks. This abnormal phenomenon led to the present study of the rational selection of test methods and objects in this context. In this study, particle size distribution, pore structure and gas desorption characteristics of coal samples in anomalous areas were analyzed. We found that desorption characteristics are related to particle size and particle size varies in relation to tectonic stress and magmatic intrusions. It appears that the anomalous readings are related to particle size of the coal, resulting from tectonic/magmatic pulverization. Furthermore, measured particle size of drill cuttings is not actually reflective of coal particle size – larger particles may be comprised of multiple smaller particles. The results show that coal samples with particle size <1 mm accounts for 76.3% of total samples and coal samples with particle size >1 mm only accounts for 23.7% of total samples. The porosity and total pore volume increase as the particle size decreases. The specific surface area increases with decreasing pore diameter. Transitional pores and micropores increase the specific surface area of the coal sample considerably. The desorption capacity increases with decreasing particle size. The additional tectonic stress caused by magmatic intrusion has a crushing effect, and 1–3 mm particles used in test were composed of a large amount of smaller particles, eventually resulting in abnormal gas desorption index phenomena. Therefore, we proposed an improved method for measuring the gas desorption index of pulverized coal.